Firm-Level Social Returns to Education - Pedro Silva Martins (Institute for the Study of Labor (IZA), 2004)
Do workers benefit from the education of their co-workers? This question is examined first by introducing a model of on-the-job schooling, which argues that educated workers may transfer part of their general skills to uneducated workers and that this spillover is affected by the degrees of non-excludability, irreversibility and generality of those skills. We then conduct an empirical analysis drawing on a matched panel of Portuguese firms and their workers. Schooling endogeneity is tackled by considering firm fixed effects and instruments based on schooling lags and the lagged share of retirement-age workers. We find evidence of large firm-level social returns (ranging between 14% and 23% – and thus exceeding standard estimates of private returns) and of significant returns accruing to less educated workers but not to their more educated colleagues.
Keywords: I20; J31; J24; 330; education; spillovers; matched employer-employee data; wages; endogenous growth; Betriebliche Bildungsarbeit; Spillover-Effekt; Bildungsertrag; Schätzung; Portugal; rent sharing